Application Database School Health Program in Primary School Level of Surabaya City - Armyade, Armyade; Wahyuni, Chatarina Umbul; Hargono, Rachmat (Faculty of Public Health, 2015)
ABSTRACTThe school health program (UKS) is a unit of the existing health activities of the primary school level. Currently the UKS programme has not been able to contribute optimally in an increasing the health of school-age children. This condition is caused due to the UKS programme planning have not been based on data and information related to health problems of school-age children. Constraints which cause yet the existence of the data and information of health problems that school age children recording and reporting system âpaper basedâ incomplete data, and delivery information is not yet in the form of graphs or tables. The purpose of this research to develop a database application UKS primary school level. The scope of this research included implementation of the UKS Trias and recording system and reporting on team Implementing the UKS primary level. This type of research was Action Research. The subject of this research team on implementing the UKS primary level I/240 Sutorejo Surabaya. System analysis of the recording and reporting of the UKS SDN 1/240 Sutorejo found the problem that is the data source that is available only the fields of health care, so that analysis can not be based on Trias UKS. This research resulted in a prototype database of UKS developed based on the results of the analysis recording and reporting system progress on implementing team UKS SDN 1/240 Sutorejo. The prototype database UKS produces health education information, health services, and health coaching school environment that can be used for program planning UKS in managing teams and Puskesmas.. The use of the UKS data base is necessary among other supporting facilities maintenance management system that aims to let the uks programme sustainabilityas well as the monitoring and evaluation activities data base system.Keywords: database, school health program, recording and reporting system.